(untitled) (Scientific journal of the Fergana State University, 2025)
This article is written about the role of mineral fertilizers in changing the agrochemical properties of light gray soils formed in Southern Fergana. Several regional negotiations are currently being held in our country on the topic of “Current situation and development trends of the international market of mineral fertilizers and related industries”.